Pengaruh Literasi Digital, Self Efficacy, Dan Motivasi Terhadap Minat Berwirausaha Generasi Z (Studi Pada Mahasiswa FEB UNISMA) - Hanim, Fadia; Mahsuni, Abdul Wahid; Utama, Satria Putra (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to determine whether digital literacy, self-efficacy, and motivation influence the entrepreneurial interest of Generation Z students at the Faculty of Economics and Business (FEB), Universitas Islam Malang. The research employs a quantitative approach using multiple linear regression analysis. Data were collected through a questionnaire with a sample of 95 respondents. The results show that, simultaneously, digital literacy, self-efficacy, and motivation influence the entrepreneurial interest of Generation Z. However, partially, only digital literacy and self-efficacy have a significant influence, while motivation does not significantly affect entrepreneurial interest. These findings emphasiZe the importance of strengthening digital literacy and self-efficacy in enhancing entrepreneurial interest among Generation Z students at FEB Unisma. Keywords: Digital Literacy, Self-Efficacy, Motivation, Entrepreneurial Interest